The Intrapersonal Intelligence in the Primary EFL Classroom: an effective medicine against school failure - García Gómez, Antonio (Pulso. Revista de educación, 2006)
The educational reform movement of recent years in Spain has spawned the search for innovative approaches to teaching. One of the most popular approaches is the theory of Multiple Intelligences posited by Howard Gardner (1983). This theory claims that there are several human intelligences that are relatively interdependent of one another and can be fashioned and combined in a multiplicity of ways by individuals and cultures (Cline, 2000). In this context, this paper relies on a six-year teaching experience in the Þ rst cycle of primary education and suggests that the intrapersonal intelligence opens and closes the door to our ability to learn new information and perform speciÞ c tasks. More precisely, this paper argues that learning a foreign language walks hand in hand with the growth of the intrapersonal intelligence. For this reason, we believe that it is important to encourage learners to explore and exercise this intelligence as a means of creating a felt meaning, a sense of relationship with the subject, in addition to an intellectual understanding (Lazear, 2003).